The relationship between the insulinemic potential of diet and lifestyle and risk of breast cancer: a case-control study among iranian adult women - Ebrahim Mokhtari; Sanaz Jamshidi; Ghazal Daftari; Hossein Farhadnejad; Farshad Teymoori; Seyed Aref Momeni; Bahram Rashidkhani; Parvin Mirmiran (BMC, 2023)
Abstract Background Breast cancer (BC) is the most prevalent cancer, with a higher mortality rate in women worldwide. We aimed to investigate the association of the insulinemic potential of diet and lifestyle with the odds of BC using empirical indices, including the empirical dietary index for hyperinsulinemia (EDIH), empirical lifestyle index for hyperinsulinemia (ELIH), the empirical dietary index for insulin resistance (EDIR), and empirical lifestyle index for insulin resistance (ELIR). Methods This hospital-based case-control study was conducted among Tehranian adult women aged≥30 years. The final analysis was performed on 134 women newly diagnosed with histologically confirmed BC as a case and 267 healthy women of the same age as control. A 168-food item food frequency questionnaire was used for assessing dietary intakes at baseline. The odds ratios (ORs) and 95% confidence intervals (CIs) of BC across tertiles of EDIH, ELIH, EDIR, and ELIR were determined using multivariable-adjusted logistic regression. Results The mean ± SD of age and BMI of participants were 47.9±10.3 years and 29.4±5.5 kg/m2, respectively. EDIH score was related to the higher risk of BC based on fully adjusted models (OR:2.24;95%CI:1.21-4.12, Ptrend=0.016). Furthermore, subgroup analysis showed a higher BC risk with increasing EDIH score in postmenopausal women (OR:1.74, 95%CI:1.13-2.69) and those without a history of the oral contraceptive pill (OCP) use (OR:1.44;95%CI:1.02-2.04). Moreover, ELIH scores were positively associated with an increased risk of BC in postmenopausal women (OR; 1.98; 95% CI: 1.35 - 2.89), those with a family history of cancer (OR:1.94;95%CI:1.10-3.42), and in individuals who did not use OCP (OR:1.46; 95% CI:1.00-2.12). Conclusion Our results showed a possible link between EDIH and higher BC risk. Also, higher EDIH and ELIH scores were strongly associated with a higher risk of BC in postmenopausal women, those with a family history of BC, and those who do not use OCP.